Identifying performance indicators for success in the European men's handball championships - Meletakos, P.; Noutsos, K.; Paulo, A.; Papavasileiou, A.; Drikos, S. (Journal of Physical Education and Sport, 2025)
Handball is a dynamic team sport that requires a combination of individual and collective performance to achieve success. Understanding the key factors that influence team performance is essential for improving strategies and player efficiency. The study aimed to show which variables can predict performance levels in top men`s handball. Data were collected from official box scores published by the European Handball Federation, which include offensive (court players` efficacy, assists and technical fouls) and defensive statistics (goalkeeper efficacy, steals, blocks, and two-minute suspensions). Data was compiled from five consecutive European handball championships, 2014-2022 (249 matches). A two-step cluster analysis was used to form three team groups, upper, middle and lower. The criterion variables per team were difference in total goals for and against, and points awarded per match played. MANOVA was used to compare all performance indicators between groups. A stepwise discriminate analysis (DA) was performed to identify performance indicator contribution to the team classification into the performance level groups. Statistical significance was set at p<0.05. Results showed significant differences in court player, goalkeeper efficacies, blocks and suspensions between the upper and lower groups. Differences were witnessed between all groups in assists, technical fouls and steals. Technical fouls and steals were found to be the key performance indicators for team discrimination. A set of performance indicators can predict the cluster grouping; thus, the game must be viewed from a multidimensional perspective.